2019
DOI: 10.1186/s40359-019-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a life-skills-based prevention program on self-esteem and risk behaviors in adolescents: a pilot study

Abstract: BackgroundRisk behaviors among young people are a major social and public health issue. This study aims to assess the impact of a life-skills-based prevention program (called Mission Papillagou) on self-esteem, well-being, and risk behaviors among adolescents.MethodIn a two-arm controlled study involving 520 school pupils aged between 10 and 15 years old, participants taking part in the prevention program (the Papillagou group) were compared to pupils who did not take part (the control group). Two assessment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, a universal CBT trial in Swedish primary schools found no evidence of long-term effects of such program on anxiety prevention [ 71 ]. Five intervention studies based on life-skill-training were found to be effective in promoting self-efficacy [ 72 , 73 ], self-esteem [ 73 , 74 ], and reducing depression/anxiety-like symptoms [ 72 , 75 , 76 ]. Courses covering stress management skills have also been reported to improve life satisfaction, increase happiness and decrease anxiety levels among students in developing countries [ 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a universal CBT trial in Swedish primary schools found no evidence of long-term effects of such program on anxiety prevention [ 71 ]. Five intervention studies based on life-skill-training were found to be effective in promoting self-efficacy [ 72 , 73 ], self-esteem [ 73 , 74 ], and reducing depression/anxiety-like symptoms [ 72 , 75 , 76 ]. Courses covering stress management skills have also been reported to improve life satisfaction, increase happiness and decrease anxiety levels among students in developing countries [ 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…When three or more manifestation types were included and compared by chi-squared test, the adjusted standardized residuals was calculated to characterize cell significance and the absolute value of adjusted residual larger than 2.58 was considered to be significant [ 18 ]. The Cramer’s V coefficients [0.1 (small); 0.3 (medium); 0.5 (large)] were used to assess the association between the categorical variables [ 19 ]. For ROC analysis, the cut-off value in the training set at the maximum of Youden index of each model was calculated and the sensitivity, specificity, accuracy in the training and testing sets were derived at such cut-off value.…”
Section: Methodsmentioning
confidence: 99%
“…These ndings further highlight theimportance of interventions that contribute to self-esteem during this stage of the life cycle (Moksnes & Espnes, 2012; Moulier et al, 2019; Zangirolami et al, 2018). Mann et al, 2004; Moulier et al, 2019; Niaraki & Rahimi, 2013; Tremblay et al, 2020; Zangirolami et al, 2018).With the excellent scores obtained here in validating the EHV-A with junior high and high school students, and the potential of schools as spaces for mental health promotion, it is now important to carry out studies with children and preadolescents(Moulier et., al, 2019;Zangirolami et al, 2018). For now, its use can be recommended in adolescents up to 17 years of age, and it can be used for fundamental decision making in mental health promotion.…”
mentioning
confidence: 90%
“…This de nition considers: 1) the importance of cognitive, interpersonal, and coping skills in adolescent psychosocial development; 2) the role of these skills on young people's ability to protect their health, adopt positive behaviors, and foster healthy relationships; 3) the development of life skills as a part of the learning and educational process that underpins adolescent well-being (Ross et al, 2020); 4) the use of these skills in other areas, such as education, violence, and human rights; 5) the reinforcement of different protective factors, such as selfknowledge, self-con dence, and self-esteem; and 6) adolescents' mastery and application of these skills in everyday situations to become more self-con dent and increase their self-e cacy and self-esteem (Botvin & Gri n, 2007;Mangrulkar et al, 2001;PAHO, 2001;Skeen et al, 2019;UNICEF, 2020;WHO, 2003WHO, , 2020. Several studies have reported an association between life skills and signi cant increases in selfesteem levels (Maryam, Davoud, & Zahra, 2011;Mohammadzadeh et al, 2019;Moulier et al, 2019), so the latter can be used as a parameter to test the external validity of life skills measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation